KONTRIBUSI EMOTIONAL ENGAGEMENT ANAK DENGAN ORANG TUA TERHADAP KECEMASAN (ANXIETY) ANAK DI TUBAN - Faradilla Mustafa; Wulan Patria Saroinsong; Suharti; Muhammad Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Anxiety disorders are a common phenomenon in early childhood that can hinder social and cognitive development. This study aims to analyze the contribution of parental emotional engagement to anxiety in children aged 4-6 years in Tuban Regency. The method used is quantitative causal-associative with a sample of 400 biological parents determined through purposive sampling across 20 sub-districts. Data were collected using Likert scale questionnaires measuring the dimensions of secure base and safe haven, as well as four anxiety dimensions in the Preschool Anxiety Scale-Revised (PAS-R). Data analysis utilized simple linear regression preceded by ex post facto. The results showed a correlation coefficient (R) of 0.419 and a significance value of 0.000 (p < 0.05). The regression equation Y = 67.198 - 0.834X indicates a significant negative relationship, where an increase in parental emotional engagement is followed by a decrease in child anxiety. An R Square value of 0.176 indicates that emotional engagement contributes 17.6% to the variation in child anxiety. These findings emphasize the importance of the parental role as an emotionally responsive figure in creating a sense of security for children. Researchers suggest the need for strengthening parenting literacy based on emotion coaching in both family and early childhood education (PAUD) environments.